Comparative study of helium bubbles in a Ti-Ta alloy and a Ti/Ta nanocomposite. (2nd July 2020) - Xiang, Sisi; McCue, Ian; Yadav, Digvijay; Wang, Yongqiang; Baldwin, Jon Kevin; Demkowicz, Michael J.; Xie, Kelvin Y.
ABSTRACT: The size, density, and distribution of helium (He) bubbles in a Ti-Ta single-phase alloy and a Ti/Ta dual-phase nanocomposite have been investigated using transmission electron microscopy. The Ti/Ta nanocomposite was fabricated via phase separation during high-temperature annealing of the single-phase Ti-Ta alloy. He ion implantation in the Ti-Ta single-phase alloy leads to the formation of nanoscale He bubbles (∼1.7 nm in size, ∼2.6 × 10 5 /μm 3 in volumetric density). He bubbles were found to segregate to grain boundaries. Under identical implantation conditions, numerous He bubbles also formed in the Ti/Ta nanocomposite. Closer inspection revealed that the He bubbles in the Ti-rich phase are smaller and of higher volumetric density (∼1.2 nm, ∼8.4 × 10 5 /μm 3 ) than those in the Ta-rich phase (∼3 nm, ∼1.8 × 10 5 /μm 3 ) and the single-phase alloy. He bubbles were also observed to decorate phase boundaries but they were generally smaller than those on grain boundaries. These results suggest that Ti/Ta phase boundaries are less conducive to the growth of large He bubbles than grain boundaries in the Ti-Ta single-phase alloy.